The Account of Joseph (Yusuf [A. S.]) in the Quran and the Bible - Opeloye, Muhib O. (2014)
The Quran, according to the Muslims' belief, is the culmination of all the revealed scriptures. Prior to its revelation, the earlier scriptures were revealed to different peoples in accordance with the requirements of their age. The Quran was revealed to the Prophet Muhammad (P. B. H.) not only to confirm the previous scriptures but also to remedy the interpolated inconsistencies found in them. It is the purpose of this paper to bring to light how the Quran performs this function with reference to Joseph's narrative. Joseph (A. S.) is the only prophet whose account is given in greater detail in one single Surah following the Biblical sequence. A close study of the Biblical account of Joseph (A.S.) reveals a number of puzzles one of which is addressed by I.A.B. Balogun in his article "Joseph in the Bible and Quran". This study is, therefore, motivated by the desire to carry further this scholarly endeavour.